HYDRODYNAMISME ET MINÉRALISATION DES EAUX SOUTERRAINES DE LA NAPPE PHRÉATIQUE PLIO-QUATERNAIRE DU PLATEAU TIMAHDITE - ALMIS GUIGOU (MOYEN ATLAS, MAROC) - Samir Amrani; Saïd Hinaje (European Scientific Journal, ESJ, 2014)
The phreatic groundwater situated in the area of study between Timahdite and Almis Guigou (Middle Atlas), is housed in training fluviolacustrine and volcanic Plio -Quaternary age. This zone corresponds to a graben or ditch, 5 km wide and 30 km long approximately. This graben is limited to the NW and SE by normal faults mean direction of N30, which is the normal age - old Middle Quaternary result of a tectonic regime extended (Hinaje, 2004). The collapse of this area is attributed to the "dawn» of the Quaternary by J. Martin (1981). From an inventory of water points and piezometric measurements during low waters (June, July and August, 2012) and during high water (January, 2013) campaign, we could establish piezometric maps. These lines show a groundwater flow groundwater Plio- Quaternary SW to NE direction. The hydraulic gradient increases towards the Almis Guigou region of NE side of the study area. The evolution of the piezometric in time shows seasonal fluctuations in relation to variations in rainfall and intermittent surges (seasonal pumping). Measurements of electrical conductivity of groundwater, as well as the results of physico- chemical analysis allowed us to define different hydrogeochemical fields. The waters are mostly calcium bicarbonate and magnesium facies of low mineralization, while water facies chloride, sulfate, calcium and magnesium strong mineralization, are mostly located near faults (infiltration and dissolution of clay-evaporitic and basaltic rocks of Triassic age).